2013
DOI: 10.1590/s1516-35982013000900008
|View full text |Cite
|
Sign up to set email alerts
|

Intake, digestibility and ruminal parameters of dairy cows fed pelleted diets and treated with lignosulfonate-containing sunflower seeds

Abstract: The objective of this study was to evaluate intake, in vitro and apparent digestibility and ruminal parameters of Holstein cows that were confined and fed corn silage and concentrate containing: ground sunflower seeds (GS); ground sunflower seeds treated with 5% lignosulfonate (GSL); pelleted sunflower seeds (PS); or ground and pelleted sunflower seeds treated with lignosulfonate (PSL). Four lactating cows with 130±28 days of lactation and body weights of 569±63 kg were used. These animals were distributed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Phipps et al (2000) administered doses of monensin (0, 150, 300, and 400 mg/d) and did not observe differences in DMI. Similar to the present study, previous works did not find effect of the thermal process in DMI (De Marchi et al, 2013;2015). Blood parameters are health indicators that can show the nutritional status and can be used to diagnose metabolic disorders.…”
Section: Discussionsupporting
confidence: 88%
“…Phipps et al (2000) administered doses of monensin (0, 150, 300, and 400 mg/d) and did not observe differences in DMI. Similar to the present study, previous works did not find effect of the thermal process in DMI (De Marchi et al, 2013;2015). Blood parameters are health indicators that can show the nutritional status and can be used to diagnose metabolic disorders.…”
Section: Discussionsupporting
confidence: 88%
“…The study revealed that TDN had not been influenced by giving dairy cattle with EEG. This result agreed with the reults reported by Marchi et al (2013) that pelleting and lignosulfonate treatments influenced diet intake and nutrient digestibility but were not affected by ground seeds. Additionally, TDN intake influenced CF, which is a source of roughage used in the diet was corn silage similar to diets based on a combination of two roughages (Alessio et al, 2018).…”
Section: Feed Consumptionsupporting
confidence: 93%
“…However, lignosulfonate and pelleting could contribute to release of oils in the rumen, improving the digestibility of nutrients and the milk production of dairy cows. Thus, studies to minimize the negative effects of high fat addition and increase PUFA uptake in milk are important to improve the impact of sunflower seeds use on ruminant nutrition (Marchi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%